2020
DOI: 10.1002/pssa.202000233
|View full text |Cite
|
Sign up to set email alerts
|

Structural, Morphological, Optical, and Electrical Properties of Sol–Gel Derived Sb‐Doped ZnO Thin Films Annealed Under Different Atmospheres

Abstract: Herein, undoped and antimony (Sb)‐doped zinc oxide (ZnO) thin films are prepared by a sol–gel spin‐coating method. The influence of different annealing atmospheres including nitrogen and argon on pertinent properties of the prepared films is scrutinized. Structural, optical, morphological, and electrical properties of all annealed films are investigated by X‐ray diffraction (XRD), field emission scanning electron microscopy (SEM), transmission electron microscopy (TEM), X‐ray photoelectron spectroscopy (XPS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…2(c) and (d)). This decreasing trend of peak broadening indicates the increase in particle size, suggesting agglomeration at a higher temperature [60,61].…”
Section: E Photocatalytic Hydrogen Evolutionmentioning
confidence: 94%
“…2(c) and (d)). This decreasing trend of peak broadening indicates the increase in particle size, suggesting agglomeration at a higher temperature [60,61].…”
Section: E Photocatalytic Hydrogen Evolutionmentioning
confidence: 94%
“…Recently, Sinornate et al 2021 synthesized ZnO thin films doped with Sb by a sol-gel spin-coating method. The decline in the crystalline property of the ZnO thin film was hugely impacted by the Sb-dopant and annealing conditions, unveiling the reduction in the NPs' size after annealing in an N, Ar environment, and upon doping [16]. The electrical resistance in the ZnO thin film can be reduced by doping it with Sb and annealing it in an N environment [17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the element Sb is often used as an effective dopant to improve the conductivity of semiconductor crystals [27,28] . The Sb 5 ion not only has a similar radius (Sb 5 radius is 0.60 Å, and the six-coordination radius of Ga 3 is 0.62 Å), but also has more valence electrons than Ga 3 [29] .…”
Section: Introductionmentioning
confidence: 99%